(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
Interactive teaching methods have largely been developed over the last two decades. Now interactive methods are considered to be modern advanced methods and they are widely used. Today, their number has exceeded 60. U. Hoshimov was engaged in the essence and purpose of these methods. Interactive methods involve activating, developing, and exploiting students ’vast educational potential. Many methodological technologies in developed countries are now multiplying interactive methods of education.